Extracellular matrix-inspired assembly of glycosaminoglycan–collagen fibers. Issue 17 (24th April 2017) - Carretero, A.; Soares da Costa, D.; Reis, R. L.; Pashkuleva, I.
Abstract : We report on the fabrication of fibers exclusively from the extracellular matrix components by interfacial complexation without using any crosslinking agent. Abstract : We report on the fabrication of fibers exclusively from the extracellular matrix components by interfacial complexation without using any crosslinking agent. The obtained fibers may have different biomedical applications as they are flexible, and cells adhere and remodel them. Moreover, their stability and thickness can be finely tuned by the sulfation degree of the used glycosaminoglycans.